MicroRNA‐17∼92 plays a causative role in lymphomagenesis by coordinating multiple oncogenic pathways. (6th August 2013) - Jin, Hyun Yong; Oda, Hiroyo; Lai, Maoyi; Skalsky, Rebecca L; Bethel, Kelly; Shepherd, Jovan; Kang, Seung Goo; Liu, Wen‐Hsien; Sabouri‐Ghomi, Mohsen; Cullen, Bryan R; Rajewsky, Klaus; Xiao, Changchun
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) have been broadly implicated in cancer, but their exact function and mechanism in carcinogenesis remain poorly understood. Elevated miR‐17∼92 expression is frequently found in human cancers, mainly due to gene amplification and Myc‐mediated transcriptional upregulation. Here we show that B cell‐specific miR‐17∼92 transgenic mice developed lymphomas with high penetrance and that, conversely, Myc‐driven lymphomagenesis stringently requires two intact alleles of miR‐17∼92. We experimentally identified miR‐17∼92 target genes by PAR‐CLIP and validated select target genes in miR‐17∼92 transgenic mice. These analyses demonstrate that miR‐17∼92 drives lymphomagenesis by suppressing the expression of multiple negative regulators of the PI3K and NFκB pathways and by inhibiting the mitochondrial apoptosis pathway. Accordingly, miR‐17∼92‐driven lymphoma cells exhibited constitutive activation of the PI3K and NFκB pathways and chemical inhibition of either pathway reduced tumour size and prolonged the survival of lymphoma‐bearing mice. These findings establish miR‐17∼92 as a powerful cancer driver that coordinates the activation of multiple oncogenic pathways, and demonstrate for the first time that chemical inhibition of miRNA downstream pathways has therapeutic value in treating cancers caused by miRNA dysregulation.